Light‐driven topochemical polymerization under organogel conditions of a symmetrical dipeptide–diacetylene system. (14th November 2016) - Mazzier, Daniela; Mosconi, Dario; Marafon, Giulia; Reheman, Aikebaier; Toniolo, Claudio; Moretto, Alessandro
Abstract : A symmetrical dipeptide‐based diacetylene system (DAs) was found to be able to self‐assemble in dichloromethane and to form a compact fiber network which resulted in a stable organogel. As a consequence of the organogel formation, we explored the possibility to run a light‐induced topochemical polymerization. This is a typical reaction of ordered diacetylene moieties taking advantage from their organized packing mode resulting from fiber formation. Evidence for the generation of peptide‐based polydiacetylenes is provided by Raman, UV–Vis, and CD spectroscopies and a set of microscopic techniques. Finally, we succeeded in processing a polymeric composite by use of the electrospinning technique, starting from a mixture of a dipeptide‐based diacetylene and polymethyl methacrylate. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A novel dipeptide‐based diacetylene system was found able to undergo to light‐induced topochemical polymerization directly from its organogel phase. The new synthetized dipeptide‐based polydiacetylene was morphologically and spectroscopically studied confirming a good degree of polymerization under these conditions.